Working households: Challenges in balancing young children and the farm enterprise. Issue 5 (19th October 2020) - Inwood, Shoshanah; Stengel, Emily
ABSTRACT: Childcare is a critical issue for working families in the United States; however childcare needs in the agriculture sector have been absent from both childcare and agricultural policy discussions. This study empirically examines the relationship between childcare, the farm business, and the farm family while probing larger questions related to quality of life, labor market outcomes, and the gendered nature of work as families negotiate on-and off-farm roles and household needs. Using data from a national survey of farm families at the Rural-Urban Interface, we highlight differences in childcare experiences among multi-generation and first-generation farmers, and men and women farmers. The majority of farmers in this sample report challenges with childcare and that these challenges affect farm business decisions. Additionally, childcare is a prevalent issue for first-generation and women farmers. To address childcare needs in rural communities and the farm population, we call for new research and engagement collaborations across community development, work and family, and farm family scholars and practitioners.